Of the three tegument proteins that package mRNA in herpes simplex virions, one (VP22) transports the mRNA to uninfected cells for expression prior to viral infection - Sciortino, Maria Teresa (The National Academy of Sciences, 2002)
An earlier report has shown that herpes simplex virus 1 virions package RNA. Experiments designed to reveal the identity of the virion proteins capable of binding the RNA and to show whether the mRNA carried in the newly infected cells was expressed showed the following: (i) (32)P-labeled riboprobe generated by in vitro transcription of the U(S)8.5 ORF bound three proteins identified as the products of U(S)11, U(L)47, and U(L)49 (VP22) genes. (ii) Viral RNA was bound to U(L)47 or U(S)11 proteins immune precipitated from cells transduced with baculoviruses expressing U(L)47 or U(S)11 and then superinfected with HSV-1 under conditions that blocked DNA synthesis and assembly of virions. (iii) Virions were purified from cells transduced with a baculovirus encoding a U(S)8.5 protein fused to green fluorescent protein and superinfected with an HSV-1 mutant lacking the U(S)8–12 genes. HEp-2 cells infected with these virions expressed the chimeric protein in ≈1% of infected cells. (iv) In mixed cultures, untreated Vero cells acquired the mRNA encoding the green fluorescent–U(S)8.5 chimeric protein from HEp-2 cells doubly transduced with the genes encoding VP22 and the chimeric protein. The transfer was RNase sensitive and VP22 dependent, indicating that the RNA encoded by the chimeric gene was transferred to Vero cells as mRNA. We conclude that (i) three virion proteins are capable of binding RNA; (ii) the packaged RNA can be expressed in newly infected cells; and (iii) the U(L)47 protein was earlier reported to shuttle from nucleus to the cytoplasm and may transport RNA. VP22 thus appears to be a member of a new class of viral proteins whose major function is to bind and transport infected cell mRNA to uninfected cells to create the environment for effective initiation of infection.